EXIT Chart Analysis of Protograph-based LDPC Codes for Unequal Power Two-User Gaussian Multiple Access Channel - Khittiwitchayakul, Sirawit; Phakphisut, Watid; Supnithi, Pornchai; Min Myint, Lin Min (My University, 2020)
In this work, we analyze the theoretical performances of protograph-based LDPC codes for unequal power two-user Gaussian multiple access channel (GMAC) by using Extrinsic information transfer (EXIT) chart. We show that the decoding performances of LDPC codes for two-users are improved significantly when the transmitted power of user increases. Moreover, we present the design of protograph structures of the LDPC codes for unequal power two-user GMAC by using the differential evolution (DE). The results show that the designed LDPC codes outperform the traditional LDPC codes.
Keywords: 2-user GMAC; Decoding threshold; Differential evolution; LDPC codes; P-EXIT chart